2014
DOI: 10.1007/s00125-014-3259-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of heart failure severity with risk of diabetes: a Danish nationwide cohort study

Abstract: Aims/hypothesis Heart failure has been suggested to increase the risk of developing diabetes. We investigated the relation between heart failure severity, defined by loop-diuretic dosage, and the risk of developing diabetes in a nationwide cohort of patients with heart failure. Methods We followed all Danish patients discharged from hospitalisation for first-time heart failure in 1997-2010, without prior use of hypoglycaemic agents, until a claimed prescription for hypoglycaemic agents, death or 31 December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
2
25
0
2
Order By: Relevance
“…13.6/1000 vs. 9.2/1000) over a 5‐year follow‐up . In a Danish nationwide cohort study, 8% of HF patients developed T2DM over 3 years, and the severity of HF was associated with a stepwise increased risk of developing T2DM . Similar incidence of T2DM was reported in clinical trials of HF patients, as demonstrated by the CHARM program, in which 7.8% of patients developed T2DM over 2.8 years .…”
Section: Epidemiologysupporting
confidence: 52%
See 1 more Smart Citation
“…13.6/1000 vs. 9.2/1000) over a 5‐year follow‐up . In a Danish nationwide cohort study, 8% of HF patients developed T2DM over 3 years, and the severity of HF was associated with a stepwise increased risk of developing T2DM . Similar incidence of T2DM was reported in clinical trials of HF patients, as demonstrated by the CHARM program, in which 7.8% of patients developed T2DM over 2.8 years .…”
Section: Epidemiologysupporting
confidence: 52%
“…Notably, HF treatment with angiotensin‐converting enzyme (ACE) inhibitors was shown to lower the incidence of T2DM in HFrEF patients; in a substudy of the SOLVD trial, 6% of patients in the enalapril arm developed T2DM over a mean follow‐up of 2.9 years as opposed to 22% in the placebo arm . Registry data corroborate that the use of renin–angiotensin system inhibitors is associated with attenuated risk for T2DM in HF patients receiving loop diuretics . Clinical trials also demonstrated that the severity of HF, as indicated by a higher New York Heart Association (NYHA) class, increases the likelihood of developing T2DM …”
Section: Epidemiologymentioning
confidence: 95%
“…We chose a priori to exclude people with prevalent cardiovascular disease and those using any antihypertensive medications (combined n =3,788 person-observations) because these conditions or the medications used to treat them have been associated with the risk of future diabetes in previous studies. [1115] Additionally, we excluded people with missing data on key covariates (age, sex, blood pressure, antihypertensive medications, cholesterol treatment, lipid values and/or blood glucose concentrations; n = 3,209).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the dosage of loop diuretic might be a proxy for metabolic disorder severity rather than heart failure severity. The higher proportion of patients with atrial flutter/ fibrillation, chronic obstructive pulmonary disease and renal disease in the higher diuretic dosage groups shown in Table 1 of the paper by Demant et al [1] not only frequently coexists with more severe heart failure, but also closely associates with more serious metabolic syndrome [6,7]. Thus, it is not clear whether more severe heart failure or more severe metabolic syndrome underlies the increased risk of diabetes in the patients receiving the higher diuretic dosage.…”
mentioning
confidence: 98%
“…
To the Editor: We read with interest the article by Demant et al [1], which reported that severity of heart failure was associated with a graduated risk of new-onset diabetes. Demant et al underscored the importance of focusing on the underlying concomitant disease and its effect on future outcomes in patients with heart failure.

However, we think that it is premature to draw a conclusion on the cause-and-effect relationship between severity of heart failure and incident diabetes.

…”
mentioning
confidence: 99%